CXCL4 triggers monocytes and macrophages to produce PDGF-BB, culminating in fibroblast activation: Implications for systemic sclerosis. Issue 111 (July 2020) - van der Kroef, Maarten; Carvalheiro, Tiago; Rossato, Marzia; de Wit, Floor; Cossu, Marta; Chouri, Eleni; Wichers, Catharina G.K.; Bekker, Cornelis P.J.; Beretta, Lorenzo; Vazirpanah, Nadia; Trombetta, Elena; Radstake, Timothy R.D.J.; et al.
Abstract: Objective: To analyze how monocyte and macrophage exposure to CXCL4 induces inflammatory and fibrotic processes observed in Systemic sclerosis (SSc) patients. Methods: In six independent experiments, monocytes of healthy controls (HC) and SSc patients were stimulated with CXCL4, TLR-ligands, IFNɑ or TGFβ and the secretion of cytokines in the supernatant was assessed by multiplex immunoassays. PDGF-BB production by monocyte-derived macrophages was quantified using immunoassays. The number of monocytes and PDGF-BB in circulation was quantified in HC and SSc patients with the Sysmex XT-1800i haematology counter and immunoassays. Intracellular PDGF-BB was quantified in monocytes by Western blot. PDGF-receptor inhibition was achieved using siRNA-mediated knockdown or treatment with Crenolanib. The production of inflammatory mediators and extracellular matrix (ECM) components by dermal fibroblasts was analyzed by qPCR, ELISA and ECM deposition assays. Results: SSc and HC monocytes released PDGF-BB upon stimulation with CXCL4. Conversely, TLR ligands, IFNɑ or TGFβ did not induce PDGF-bb release. PDGF-BB plasma levels were significantly ( P  = 0.009) higher in diffuse SSc patients (n = 19), compared with HC (n = 21). In healthy dermal fibroblasts, PDGF-BB enhanced TNFɑ-induced expression of inflammatory cytokines and increased ECM production. Comparable results were observed in fibroblasts cultured in supernatant taken from macrophages stimulated with CXCL4. This effect was almost completely abrogated by inhibition of the PDGF-receptor using Crenolanib. Conclusion: Our findings demonstrate that CXCL4 can drive fibroblast activation indirectly via PDGF-BB production by myeloid cells. Hence, targeting PDGF-BB or CXCL4-induced PDGF-BB release could be clinically beneficial for patients with SSc. Highlights: PDGF-BB is increased in the circulation of patients with diffuse systemic sclerosis. CXCL4 specifically induces the release of PDGF-BB by monocytes and macrophages. PDGF-BB potentiates the inflammatory and fibrotic phenotype in dermal fibroblasts. CXCL4-conditioned M2 macrophages activate fibroblasts causing ECM deposition. Crenolanib abrogates fibroblast activation induced by PDGF-BB.